Determinación del grado de partículas atmosféricas sedimentables, mediante el método de Muestreo Pasivo, zona urbana – ciudad de Moyobamba, 2012. - Lozano Coral, Freddy Rusber (2013)
The Moyobamba city is no stranger to the exposure of the pollutants such as sedimentary particles that are generated due to urban growth, the increase in traffic, urban sprawl in the unpaved streets, the development of production activities for combustion of renewable energies such as sources of energy, the lack of zoning in the various companies, among other aspects, generate this great problem of air pollution. Through this investigation work that was conducted in the Moyobamba city since the month of October 2012 the month of January 2013, it was determined the degree of sedimentary particle in our city, for which it was established 15 monitoring stations where you applied the methodology of Passive Sampling, that was in the placement of petri dishes located on the second level of dwellings, for thirty (30) days during 03 months. For the location of the stations to monitor took into account the type of track, population density and traffic; Achieving this determine with 03 sample areas in the Moyobamba city: Center, Intermediate, and periphery locating at home zone 05 monitoring stations. The results obtained of the monitoring deposited matter, an average final value of 0.70 was obtained mg/cm2 - Month on the stations of sampling, exceeding this way the Standards of Environmental Quality for Deposited matters in 0.20 mg/cm2 - Month established by the World Health Organization OMS, which is of 0.50 mg/cm2 - month as maximum value. According to the results of the monitoring of the sedimentary particles was determined the existence of a direct relationship between weather conditions and the generation of sedimentary particle, in the months of highest precipitation is recorded the lowest amount of sedimentary particle in comparison with the month of less precipitation recorded a greater amount of sedimentary particle. In addition the applied analysis of the variance in where it was determined that there was no significant difference between the data obtained, but that if they help to determine that there is a problem of environmental pollution that with this project will contribute to make a call for attention to the general public in favor of sustainable development and quality of life that we all crave.